Efficacy, safety and complications of autologous fat grafting to healthy breast tissue: A systematic review - Largo, Rene D.; Tchang, Laurent A.H.; Mele, Valentina; Scherberich, Arnaud; Harder, Yves; Wettstein, Reto; Schaefer, Dirk J. (Journal of plastic, reconstructive & aesthetic surgery, 2014)
Fat grafting for primary breast augmentation is growing in popularity due to its autologous properties and its side benefit of removing unwanted fat from other areas, although volume gain is unpredictable and patient safety remains unclear. The aim of this study was to provide an evidence-based overview of autologous fat grafting to healthy breast tissue with focus on volume gain, safety and complications. A systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The MEDLINE, Cochrane Library and EMBASE databases were searched for clinical studies on autologous fat grafting to healthy breast tissue within the last 30 years. Clinical articles were evaluated for indication, pre- and postoperative work-up, surgical technique, volume gain (efficacy), complications, radiographic changes and oncological safety. The level of evidence was assessed according to the Oxford Centre for Evidence-based Medicine 2011. A total of 36 articles involving 1453 patients with a mean follow-up period of 16.3 months (1–156 months) were included. No randomised controlled studies were found. Six percent of the patients undergoing fat grafting to healthy breast tissue experienced major complications requiring a surgical intervention or hospitalisation. Two patients with breast cancer (0.1%) after fat grafting for cosmetic purposes were reported. Average breast volume gain ranged from 55% to 82% relative to the grafted fat volume. The prevalence of complications and re-operations in fat grafting to healthy breast tissue compared favourably to implant-based breast augmentation. Although no increased incidence of breast cancer was found, long-term breast cancer screening and the implementation of publicly accessible registries are critically important to proving the safety of fat grafting.